Airport Development Impact On The Sustainable Development Of The National Tourism Industry - Alaeerad, Elham; Khoshnood, Mohsen (The Turkish Online Journal of Design Art and Communication, 2016)
With the development of transportation industry especially in air transportation and the increase in the number of inland and outland journeys, tourism has gradually taken a new form and nowadays it is a lucrative and infinite industry. Tourism as a stable economical source with high financial turnover is considered to be an important economical source especially in developed and powerful countries and is specifically considered as an important topic to achieve economic development in underdevelopment countries. Developing state of any community is also apparent from its ability in international communication. Among these, airports can be mentioned as one of the most important gates of communication, the development of which can be considered as a major step in improving development of a country. In this article we are trying to not only present correct definitions of tourism and sustainable development, and explain features, capabilities and deficiencies in the aviation industry and provide suitable planning and strategies, but also to improve tourism and consequently increase national income.
Keywords: Sustainable development; Tourism; Aviation industry; Airport